Primary intestinal type mucinous adenocarcinoma of the ovary diagnosed during pregnancy – Maternal and neonatal treatment and outcomes: A case report - Hase, Eliane Azeka; Shinohara, Henrique Norio; Alves Filho, João Alberto Garcia; Sadalla, José Carlos; Ab́saber, Alexandre Muxfeldt; Francisco, Rossana Pulcineli Vieira (Frontiers in Medicine, 2023)
The incidence of ovarian cancer during pregnancy is low. Most adnexal tumors removed during pregnancy are benign, with ovarian carcinomas found in approximately 1: 10,000–1:50,000 pregnancies. Literature on this disease is scarce and consists mostly of retrospective studies and case reports. We report the case of a pregnant patient who presented with a primary intestinal-type mucinous adenocarcinoma of the ovary and underwent unilateral salpingo-oophorectomy, with no additional surgical or chemotherapy treatment after the histological diagnosis, despite an infiltrative stromal invasion pattern. To the best of our knowledge, no such case has been previously reported. Conservative treatment in this case of early ovarian carcinoma is possible during pregnancy and should be performed in the Department of Gynecological Oncology and Obstetrics of a tertiary referral hospital. Given the possibility of disease recurrence, such patients require strict clinical oncological surveillance, specialized prenatal care, and assistance from a multidisciplinary team to improve the maternal and perinatal outcomes.